Studies on various aspects of the vanadium chemistry of the Stretford process - Falkiner, J. (My University, 1978)
This work touches on a wide variety of subjects with the vanadium process chemistry in the Stretford Process. A comprehensive literature survey of desulfurization systems is presented in chapter 1 and appendix II. Experimental work is focused on vanadium oxidation, reduction, and precipitation in Stretford-like solutions.
Keywords: Biology; Biology